High Frequency of Fetal Loss in Fetuses With Normal Karyotype and Nuchal Translucency ≥ 3 Among the Iranian Pregnant Women - Shokoh Abotorabi; Niloufar Moeini; Sahar Moghbelinejad (Tehran University of Medical Sciences, 2020)
Objective: The purpose of this study was comparison of association of three main first trimester screening factors with pregnancy outcomes among Iranian pregnant women. Materials and methods: This prospective study was done during 2017-2019 years in Qazvin, Iran. To do so, a total of 1500pregnant women in first trimester were enrolled. At the first step, Nuchal translucency (NT) was measured in 11-13 ± 5 week, then the serum pregnancy-associated plasma protein A (PAPP-A) and free-β-human chorionic gonadotropin (free-β-HCG) were measured in 12-14 weeks of gestation. Pregnant women were followed up until the end of pregnancy for the complications of pregnancy such as intra-uterine growth retardation (IUGR), intrauterine death (IUFD), different types of fetal loss and preterm labor. Results: The results showed that low levels of serum biomarkers had more association with pregnancy complications in comparison to high levels of them. Significant association of IUGR (P = 0.001), IUFD (P = 0.032) and pre-term labor (P = 0.002) was shown in women with low serum levels of PAPP-A in comparison to low serum levels of free-β-hCG. Significant high frequency of different types of fetal loss (IUFD, Abortion, Elective termination) was shown in fetuses with N ≥ 3 in comparison to low levels of serum biomarkers (P = 0.001). Conclusion: This study highlighted the importance of accurately interpreting the results of the first trimester of pregnancy screening which should be considered by primatologists for subsequent pregnancy care.